A 12‐month follow‐up study on the preventive effect of oral lansoprazole on acute exacerbation of chronic obstructive pulmonary disease. Issue 2 (2nd May 2016) - Xiong, Wei; Zhang, Quan‐san; Zhao, Wei; Ding, Wei; Liu, Jin‐ming; Zhao, Yun‐feng
Abstract : Summary: The objective of this study was to evaluate the preventive effects of oral administration of lansoprazole on acute exacerbation of chronic obstructive pulmonary disease (COPD). Patients with COPD in groups C and D in the stable phase were stratified into a group with neither gastroesophageal reflux nor lansoprazole therapy (group A) and a group subjected to oral lansoprazole therapy (group B1 ) and a group not subjected to oral lansoprazole therapy (group B2 ). The frequency scale for the symptoms of gastroesophageal reflux disease (FSSG) questionnaire, COPD assessment test (CAT) questionnaire, pulmonary function test and the 6‐minute walk test were applied; in addition, arterial blood gas, white blood cell (WBC), hs‐CRP, liver function and the levels of IL‐1β, IL‐6, IL‐8, TNF‐α and GM‐CSF in sputum were monitored during follow‐up. In the 12‐month follow‐up period, the frequency of exacerbation in group B2 was statistically higher than that in groups A and B1 ( P  <   0.05). After a 3‐month follow‐up, the score of groups A and B1 in the FSSG questionnaire was significantly lower than that of group B2 ( P  <   0.05). After the 1‐year follow‐up, the CAT score, FEV1, 6‐min walk test, the total number of WBC, hs‐CRP, alanine aminotransferase, aspartate aminotransferase, pH of the arterial blood, PaO2, PaCO2 and the levels of IL‐1β, IL‐6, IL‐8, TNF‐α and GM‐CSF in the sputum were statistically different in group B2 compared with groups A and B1 ( P  < 0.05). Oral lansoprazole therapy decreased the frequency of acute exacerbation of COPD by alleviating gastroesophageal reflux and lowering the levels of IL‐1β, IL‐6, IL‐8, TNF‐α and GM‐CSF in the sputum.